United States : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This Selected Issues paper focuses on U.S. potential growth in the aftermath of the crisis. It discusses recent productivity developments in the nonfarm business sector. The paper uses back-of-the envelope calculations to gauge the effect of diminished financial sector activity on GDP growth in coming years. A simple production function framework is used to give a long view of key factors explaining potential GDP growth in the United States in the last 30 years and explore possible developments in the next few years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet